Important outcomes of moral case deliberation: a Euro-MCD field survey of healthcare professionals' priorities. Issue 9 (18th July 2019) - Svantesson, Mia; de Snoo-Trimp, Janine C; Ursin, Göril; de Vet, Henrica CW; Brinchmann, Berit S; Molewijk, Bert
Abstract : Background: There is a lack of empirical research regarding the outcomes of such clinical ethics support methods as moral case deliberation (MCD). Empirical research in how healthcare professionals perceive potential outcomes is needed in order to evaluate the value and effectiveness of ethics support; and help to design future outcomes research. The aim was to use the European Moral Case Deliberation Outcome Instrument (Euro-MCD) instrument to examine the importance of various MCD outcomes, according to healthcare professionals, prior to participation. Methods: A North European field survey among healthcare professionals drawn from 73 workplaces in a variety of healthcare settings in the Netherlands, Norway and Sweden. The Euro-MCD instrument was used. Results: All outcomes regarding the domains of moral reflexivity, moral attitude, emotional support, collaboration, impact at organisational level and concrete results, were perceived as very or quite important by 76%–97% of the 703 respondents. Outcomes regarding collaboration and concrete results were perceived as most important. Outcomes assessed as least important were mostly about moral attitude. 'Better interactions with patient/family' emerged as a new domain from the qualitative analysis. Dutch respondents perceived most of the outcomes as significantly less important than the Scandinavians, especially regarding emotional support. Furthermore, men, those who were younger, and physician-respondents scored most of the outcomes as statistically significantly less important compared with the other respondents. Conclusions: The findings indicate a need for a broad instrument such as the Euro-MCD. Outcomes related to better interactions between professionals and patients must also be included in the future. The empirical findings raise the normative question of whether outcomes that were perceived as less important, such as moral reflexivity and moral attitude outcomes, should still be included. In the future, a combination of empirical findings (practice) and normative reflection (theories) will contribute to the revision of the instrument.